Avskrift av dagbok ført på Eirik Raudes land (Kong Kristian Xdes land) 1932-1933 - Hofgård, Knut; Sørensen, Sverre J.; Marø, Bernt K.; Brandal, Leif J.; Thorstensen, John; Nakken, Knut; Molt, Walter; Furland, Hans; Tolløfsen, Sigurd (1933)
DAG-150